The Influence of Transformational Leadership of School Principals on the Performance of Junior High School Teachers in North Panajem Paser Regency - Rahayu, Endang Sri; Rifqi, Ainur; Haq, Mohammad Syahidul; Khamidi, Amrozi (Journal of English Language and Education, 2026)
Principal leadership is widely recognized as a crucial factor in determining the quality of teacher performance in schools. Numerous studies have examined the relationship between leadership styles and teacher performance; however, empirical evidence in developing regions and newly transforming areas remains limited. In particular, there is still a lack of empirical studies investigating transformational leadership in schools located in regions undergoing rapid socio-educational transformation, such as Penajam Paser Utara Regency in East Kalimantan, which serves as a buffer area for Indonesia’s new capital city (IKN). This study aims to examine the effect of transformational leadership of school principals on the performance of junior high school teachers in Penajam Paser Utara Regency. The research employed a quantitative approach with a causal ex post facto design. The sample consisted of 253 teachers selected through stratified cluster random sampling from a population of 520 teachers. Data were collected using a four-point Likert-scale questionnaire that had been tested for validity and reliability, and were analyzed using simple linear regression with SPSS version 22. The results indicate that transformational leadership has a positive and significant effect on teacher performance, with a significance value below 0.05. These findings suggest that the more effectively principals implement transformational leadership practices, the higher the level of teacher performance.